The Role of Sulfide Minerals and Carbon in The Pretreatment of Refractory Gold Ores with Chlorine - Hendrix J. L; Nelson J. H (The Australasian Institute of Mining and Metallurgy, 1991)
A study was conducted to examine how pretreatment of carbon-bearing gold ores with chlorine enhances gold recovery by cyanidation. It is hypothesized that metal species (including iron and copper) dissolved during chlorination adsorb on the carbon surface hindering the adsorption of dissolved gold. To test the hypothesis, samples of several sulfide minerals were subjected to reaction with sparged chlorine gas to determine which, if any, dissolve faster than gold under these conditions. Then, a synthetic carbonaceous refractory gold ore containing pyrite, chalcocite, activated carbon, and gold was subjected to gas sparging. The results of these experiments showed that chalcocite and arsenopyrite dissolve so that metal (copper and iron) is put into solution slightly faster than gold under the same chlorination conditions. Also, it was observed from the experiments that gold adsorbs on activated carbon during chlorination, but is replaced by copper and iron as the chlorination process dissolves more of the chalcocite and pyrite. The study concluded by investigating ferric chloride addition prior to chlorination to hinder gold adsorption on activated carbon.